Influence of Self-Care Guidelines on Improving Menopausal Urogenital Symptoms - Mona Ahmed ElSheikh; Aziza Ahmed Atia; Nevin Samir Metwaly; Laila Ahmed Nabwy (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the effect of self-care guidelines on improving menopausal urogenital symptoms. Method: The quasi-experimental study was conducted from September 2018 to February 2019 at the outpatient clinic at the maternity hospital of Ain Shams University, Egypt, and comprised menopausal women reporting urogenital symptoms. The participants were divided into 10 equal groups and were subjected to 30-minute theoretical and practical self-care sessions 3 times per week for 4 weeks. Data was collected using interviews, Day-to-Day Impact of Vaginal Aging questionnaire and Urinary Incontinence Questionnaire. Data was collected at baseline, immediately after the intervention and after 3 months from the first evaluation. The collected data were statistically analysed using the statistical package for social science (SPSS version 20), percentage (%), the arithmetic mean (), standard deviation (SD), and chi-square (X2 & P-value) were calculated. Results: Of the 120 women with mean age 48.03±3.04 years (range: 45-50 years), 72(60%) had secondary education, 109(90.8%) were married, 44(36.7%) were working in an office and 7(55.8%) were housewives. The mean age at menopause was 46.57±2.33 years (range: 42-50 years). Urogenital symptoms post-intervention reduced significantly (p<0.05) Conclusion: Self-care intervention had a significant impact in terms of improving menopausal urogenital symptoms. Keywords: Gynaecology, Menopause, Urinary incontinence, Ambulatory care, Urinary tract, Aging, Urogenital symptoms.